Surrogate Markers of Insulin Resistance to Predict the Prognosis of COVID-19 Disease: A Retrospective Analysis - Susmita Banerjee; Shuvankar Mukherjee; Sukla Mitra (Journal of Clinical and Diagnostic Research)
Introduction: Coronavirus Disease-2019 (COVID-19) patients exhibit an extensive range of disease manifestations. Disturbances in metabolic and lipid profiles occur due to the release of cytokines. The lipid elements of the COVID-19 virus play a significant role in the fusion of the viral membrane to the host cell, in addition to replication. Although the COVID-19 scenario is multifaceted, high risks are observed in patients with co-morbidities such as Insulin Resistance (IR). Lipid ratios and the Triglyceride-Glucose index (TyG) could serve as simple biochemical markers of IR, thereby aiding in the assessment of prognosis in admitted COVID-19 patients, particularly those with comorbid conditions like IR. Aim: To assess the severity of COVID-19 infection based on lipid ratios and the TyG index. Materials and Methods: This retrospective study was conducted at Diamond Harbour Government Medical College and Hospital, 24 Parganas, West Bengal, India, data from 189 diagnosed COVID-19 patients, aged between 18 and 60 years in and around diamond harbour, were collected after obtaining the necessary ethical clearance. All the patients, including referred cases, were admitted to the COVID-19 ward of Diamond Harbour Government Medical College and Hospital. Data from biochemical tests, such as Fasting Blood Glucose (FBG), Total Cholesterol (TC), Triglycerides (TG), Low-Density Lipoprotein (LDL), High-Density Lipoprotein (HDL) and C-Reactive Protein (CRP), which were analysed using an autoanalyser (Transasia XL 640), were recorded. The lipid ratios and TyG index were calculated. The optimal cut-off values for all the above indices were derived from the point with the maximum Youden index by plotting the Receiver Operating Curve (ROC). Statistical analysis was performed using Statistical Package for the Social Sciences (SPSS) Software version 20. Results: The Fasting Blood Sugar (FBS), TG, TG/HDL, TC/HDL and TyG index levels were significantly higher in the severe COVID-19 patients (p<0.05). The optimal cut-off values calculated for the TyG index, TG/HDL and TC/HDL were 9.34, 3.55 and 3.83, respectively. Conclusion: In COVID-19 patients, a TyG index and lipid ratios of TG/HDL and TC/HDL exceeding 9.34, 3.55 and 3.83, respectively, could serve as early indicators of COVID-19 severity, thus assisting in the assessment of prognosis.